Recognizing Psychiatric Comorbidity With Reading Disorders - Hendren, Robert L.; Haft, Stephanie L.; Black, Jessica M.; White, Nancy Cushen; Hoeft, Fumiko (Frontiers in Psychiatry, 2018)
Reading Disorders (RDs), a specific learning disorder of reading that includes impairment in word reading, reading fluency and/or reading comprehension, are common in the general population but often are not comprehensively understood or assessed in mental health settings. In education settings, comorbid mental and associated disorders may be inadequately integrated into intervention plans. Assessment and intervention for RD may be delayed or absent in children with frequently co-occurring mental disorders not fully responding to treatment in both school and mental health settings. To address this oversight, this review summarizes current knowledge regarding RDs and common comorbid or co-occurring disorders that are important for mental health and school settings. We chose to highlight RD because it is the most common specific learning disorder and connections to other often comorbid disorders has been more thoroughly described in the literature. Much of the literature we describe is on decoding-based RD (or developmental dyslexia) as it is the most common form of RD. In addition to risk for academic struggle and social, emotional, and behavioral problems, those with RD often show early evidence of combined or intertwined DSM-5 (Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition) childhood disorders. These include attention deficit hyperactivity disorder, anxiety and depression, disruptive, impulse-control, and conduct disorders, autism spectrum disorders, and other specific learning disorders. The present review highlights issues and areas of controversy within these comorbidities, as well as directions for future research. An interdisciplinary, integrated approach between mental health professionals and educators can lead to comprehensive and targeted treatments encompassing both academic and mental health interventions. Such targeted treatments may contribute to improved educational and health-related outcomes in vulnerable youth. While there is a growing research literature on this association, more studies are needed of when to intervene and of the early and long-term benefits of comprehensive intervention.